2021
DOI: 10.3390/antiox10040567
|View full text |Cite
|
Sign up to set email alerts
|

Wolfberry (Lycium barbarum) Consumption with a Healthy Dietary Pattern Lowers Oxidative Stress in Middle-Aged and Older Adults: A Randomized Controlled Trial

Abstract: Incorporating zeaxanthin-rich wolfberry (Lycium barbarum) into a healthy dietary pattern may augment its antioxidant potential. The present 16-week, parallel design randomized controlled trial aimed to investigate the impact of adhering to a healthy dietary pattern, either with or without whole dried wolfberry (15 g/d) on oxidative stress status (plasma malondialdehyde and 8-iso-prostaglandin F2α) in middle-aged and older adults. Changes to carotenoids status (plasma and skin carotenoids) and body composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Wolfberry (Lycium barbarum L., 2n = 2x = 24), of the genus Lycium within the Solanaceae family, is an important Chinese traditional herbal medicine [1]. The fruits are a rich source of carotenoids, flavonoids, and polysaccharides, contributing to wolfberry's immuneenhancing, antioxidant, and anti-tumor effects [2][3][4]. The carotenoids are responsible for L. barbarum fruit colorations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Wolfberry (Lycium barbarum L., 2n = 2x = 24), of the genus Lycium within the Solanaceae family, is an important Chinese traditional herbal medicine [1]. The fruits are a rich source of carotenoids, flavonoids, and polysaccharides, contributing to wolfberry's immuneenhancing, antioxidant, and anti-tumor effects [2][3][4]. The carotenoids are responsible for L. barbarum fruit colorations [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Associations between the plasma lipidomic changes and the corresponding effects on a panel of CVD-related risk indicators ( n = 47) and nutrition/dietary information ( n = 35) were studied ( 20 , 21 ). Main effects (i.e., between lipid species and outcome of interest) are summarized in heat maps ( Supplementary Figure 4 ) with the main effect size and Q values of significant pairs additionally detailed in Supplementary Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by wolfberry-based clinical trials which reported favorable changes to blood lipid-lipoproteins following a 3 months intervention with L. barbarum polysaccharides (100 mg/kg body weight daily) and a 45-day intervention with whole wolfberry (14 g dried fruit per day) ( 17 19 ). Previously, we demonstrated notable improvements in HDL cholesterol (HDL-C) concentration ( 20 ) and oxidative stress status ( 21 ) following the consumption of 15 g/day whole wolfberry with a HDP for 16 weeks. Nevertheless, limited studies examined these blood lipid changes in detail and the potential mechanisms that underlie the observed cardiovascular protective benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they observed an inverse association between the changes in plasma zeaxanthin and plasma 8-iso-prostaglandin F2α. Therefore, goji berry within a healthy dietary pattern is proposed as a dietary strategy to attenuate lipid peroxidation among middle-aged and older adults, with a heightened risk of oxidative stress-induced age-related disorders [ 95 ].…”
Section: Health Benefits and Side Effects Of Goji Berry Consumptionmentioning
confidence: 99%